Transformation of Beauty in Digital Fine Arts Aesthetics: An Artpreneur Perspective - Wiratno, Tri Aru; Callula, Brigitta (Aptisi Transactions On Technopreneurship (ATT), 2024)
The evolving nature of beauty in digital fine arts aesthetics signifies profound shifts within contemporary social and cultural contexts. Technological advancements have enabled artists to explore new mediums, creating works that reflect and respond to current societal issues. This study examines the paradigm shift in digital fine arts, focusing on the interpretation and manifestation of beauty in digital creations. It explores the interplay between digital aesthetics and societal realities, providing insights into the transformation of beauty in the digital age. An interdisciplinary approach is utilized, incorporating textual analysis of relevant literature, participatory observation at art exhibitions and online platforms, and a comprehensive literature review. These methods trace the evolution of beauty in digital fine arts and analyze how artists incorporate visual, auditory, and interactive elements. The research demonstrates that technological progress has significantly impacted the creation and perception of beauty in fine arts. This transformation includes broader definitions of aesthetics, integrating multisensory experiences and community participation. Digital fine arts now serve as a dynamic medium that reflects diverse social, political, and cultural themes. The transformation of beauty in this field underscores the complex relationships among art, technology, and society. Digital artworks provide innovative aesthetic experiences and mirror contemporary social dynamics. Despite concerns regarding the authenticity and preservation of digital art, its role in expanding artistic expression and fostering innovation is undeniable